THE LANGUAGE OF RELIGIOUS TOLERANCE AND POLITICAL PUBLICITY APPROACHING THE GUBERNATORIAL ELECTION OF DKI JAKARTA IN THE SOCIAL MEDIA - Eva Leiliyanti; Diyantari Diyantari (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
The upcoming gubernatorial election of Jakarta province (pilkada) in 2017 can arguably be perceived as the arena where the scrutiny of the relationship between (religious) majority and minority groups controversially takes place. In the stage of constructing the positive political image of the candidate, the supporters/volunteers at the same time counter, criticize and contest the political image the opponents’ construct. One of the supporters/volunteers who perpetually demonstrate their faithful support for the incumbent governor is Jasmev (Jokowi Ahok Media Volunteer). Deploying Hallidayian transitivity system, this paper focuses on the language Jasmev employed in the constructing Basuki Tjahaja Purnama’s (Ahok) image and contesting the opponents’ image in the Facebook. They position Ahok as the most suitable candidate that is believed capable in accelerating the urban and city development of Jakarta. Ahok is also framed in the language that purportedly exhibits religious tolerance, social equity and equality, clean and accountable governance. The data were taken since the moment Ahok declared himself as the candidate up to September 2016. It was found that the language they deployed lies in the obscurity of the negative and black campaign, especially when they contest the political image of their opponents.